A high-efficiency ultraviolet light-curing adhesive composition and its preparation method and application

By optimizing the composition and system of ultraviolet curing adhesives, including monofunctional acrylate monomers, modified bifunctional aliphatic polyurethane acrylate oligomers, etc., the problem that existing adhesives are difficult to completely cure in the light-blocking area is solved, efficient dark curing and crack resistance are achieved, and packaging quality and reliability are improved.

CN119752390APending Publication Date: 2025-04-04SHENZHEN NO 1 FINE CHEM CO LTD

Patent Information

Application Number
CN202411887347.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the use of existing ultraviolet curing adhesives, due to being blocked by electronic components, it is difficult to fully cure the unirradiated areas, resulting in limited adhesion and curing depth of the adhesive after curing. In addition, temperature fluctuations can easily cause delamination and debonding between the adhesive and the circuit board, thereby affecting the packaging effect.

Method used

Provided is a highly efficient ultraviolet curing adhesive composition, including monofunctional acrylate monomer, modified bifunctional aliphatic polyurethane acrylate oligomer, photoinitiator, photosensitizer, heat initiator and light scattering filler. By optimizing the main resin and photoinitiation system, rapid curing and dark curing are achieved, and temperature stability and crack resistance are improved.

Benefits of technology

This adhesive not only has a rapid curing effect in areas with sufficient light, but also further cures by micro-heat in the light blocking area. It has excellent dark curing, delayed curing and crack resistance, improves light transmittance, temperature stability and adhesion, and effectively improves packaging quality and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199695690000011
    Figure BDA0005199695690000011
  • Figure BDA0005199695690000021
    Figure BDA0005199695690000021
  • Figure BDA0005199695690000031
    Figure BDA0005199695690000031
Patent Text Reader

Abstract

The present invention belongs to the technical field of adhesives, and provides a high-efficiency ultraviolet light-curing adhesive composition, a preparation method thereof, and an application thereof. The high-efficiency ultraviolet light-curing adhesive composition of the present invention comprises the following components in parts by weight: 30 to 60 parts of monofunctional acrylate monomers, 10 to 30 parts of modified difunctional aliphatic polyurethane acrylate oligomers, 2 to 5 parts of photoinitiators, 0.5 to 2 parts of photosensitizers, 0.1 to 1 parts of thermal initiators, and 0.01 to 0.1 parts of light-scattering fillers. The high-efficiency ultraviolet light-curing adhesive composition of the present invention optimizes the main resin and the photoinitiator system, and not only has a rapid curing effect in areas with sufficient light, but also has a continuous free radical generation ability after the light stops. It can be further cured by micro-heat in light-shielded areas, has excellent dark curing, delayed curing and crack resistance, improves light transmittance, temperature stability and adhesion, and effectively improves packaging quality and reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a high-efficiency ultraviolet light-curing adhesive composition, a preparation method thereof and an application thereof. Background Art

[0002] Mini LED is a new type of LED display technology derived from small-pitch LED, also known as sub-millimeter light-emitting diode. Its grain size is about 100-200μm, which is between traditional LED and Micro LED. Its comprehensive cost and luminous efficiency have huge industry development potential. Mini LED generally consists of three parts: Mini LED light-emitting chip, packaging substrate and optical adhesive layer, of which the optical adhesive layer is located on the surface of the packaging substrate to fix and protect the Mini LED light-emitting chip.

[0003] Chinese patent CN114181660A discloses a UV-curable adhesive composition for Mini LED packaging, and its preparation method and application. The UV-curable adhesive composition comprises a monofunctional acrylate monomer, a monofunctional or difunctional polyurethane acrylate oligomer, a photoinitiator and a silane coupling agent. The UV-curable adhesive composition can be cured quickly, and has low viscosity, moderate hardness, high light transmittance and good weather resistance after curing, and has a certain curing depth. However, during the use of the above-mentioned UV-curable adhesive, it is difficult to achieve complete curing in the unirradiated area due to the obstruction of electronic components, resulting in the adhesion and curing depth of the adhesive after curing being limited. In addition, temperature fluctuations can easily cause delamination and debonding between the adhesive and the circuit board, thereby affecting the packaging effect.

[0004] Therefore, the development of an efficient UV-curing adhesive that can fully cure even the unirradiated areas while also having excellent temperature stability and crack resistance has broad application prospects. Summary of the invention

[0005] The object of the present invention is to provide a high-efficiency ultraviolet light-curing adhesive composition and a preparation method and application thereof in view of the deficiencies in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a high-efficiency ultraviolet light-curing adhesive composition, comprising the following components in parts by weight:

[0008]

[0009]

[0010] Preferably, the monofunctional acrylate monomers include isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate, and the mass ratio of isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate is 5-7:2-4:1.

[0011] Preferably, the modified difunctional aliphatic urethane acrylate oligomer comprises a polycaprolactone-modified difunctional aliphatic urethane acrylate oligomer, a polycarbonate-modified difunctional aliphatic urethane acrylate oligomer and a polyether-modified difunctional aliphatic urethane acrylate oligomer, and the mass ratio of the polycaprolactone-modified difunctional aliphatic urethane acrylate oligomer, the polycarbonate-modified difunctional aliphatic urethane acrylate oligomer and the polyether-modified difunctional aliphatic urethane acrylate oligomer is 5 to 7:2 to 4:1.

[0012] Preferably, the photoinitiator comprises phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and the mass ratio of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide to ethyl 2,4,6-trimethylbenzoylphenylphosphonate is 80-90:15.

[0013] Preferably, the photosensitizer is 2-chlorothioxanthone or thioxanthone.

[0014] Preferably, the thermal initiator is tert-butyl peroxypivalate or dicumyl peroxide.

[0015] Preferably, the light scattering filler is nano titanium dioxide or nano silicon dioxide.

[0016] The present invention also provides a method for preparing the high-efficiency UV-curable adhesive composition, comprising the following steps:

[0017] A high-efficiency ultraviolet light-curing adhesive composition is obtained by mixing monofunctional acrylate monomers, modified bifunctional aliphatic polyurethane acrylate oligomers, photoinitiators, photosensitizers, thermal initiators and light-scattering fillers.

[0018] Preferably, the mixing temperature is 30-50° C., the mixing time is 20-30 min, and stirring is performed during the mixing process at a stirring speed of 300-600 rpm.

[0019] The present invention also provides application of the high-efficiency UV-curable adhesive composition in Mini LED packaging.

[0020] The beneficial effects of the present invention include the following:

[0021] 1) The high-efficiency UV-curable adhesive composition of the present invention optimizes the main resin and the photoinitiator system, and not only has a rapid curing effect in areas with sufficient light, but also has a continuous free radical generation ability after the light stops. It can be further cured by micro-heat in light-shielded areas, and has excellent dark curing, delayed curing and crack resistance. It has improved light transmittance, temperature stability and adhesion, effectively improves packaging quality and reliability, and meets Mini LED packaging requirements.

[0022] 2) The high-efficiency UV-curable adhesive composition of the present invention has a viscosity of 500-900 cps, a Shore hardness of 30-60, a curing depth of 2.5-3 mm, a light transmittance of up to 93%, and a light transmittance of 91% after aging testing. It does not debond or crack at low temperatures of -40°C and high temperatures of 80°C, and has excellent comprehensive performance. DETAILED DESCRIPTION

[0023] The present invention provides a high-efficiency ultraviolet light-curing adhesive composition, comprising the following components in parts by weight:

[0024]

[0025] In the present invention, in parts by mass, the monofunctional acrylate monomer is 30 to 60 parts, preferably 35 to 55 parts, more preferably 40 to 50 parts, and more preferably 45 parts; the modified bifunctional aliphatic polyurethane acrylate oligomer is 10 to 30 parts, preferably 15 to 25 parts, and more preferably 20 parts; the photoinitiator is 2 to 5 parts, preferably 3 to 4 parts; the photosensitizer is 0.5 to 2 parts, preferably 1 to 1.5 parts; the thermal initiator is 0.1 to 1 part, preferably 0.3 to 0.8 parts, and more preferably 0.5 parts; the light scattering filler is 0.01 to 0.1 parts, preferably 0.03 to 0.08 parts, and more preferably 0.05 parts.

[0026] In the present invention, the monofunctional acrylate monomer preferably comprises isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate, and the mass ratio of isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate is preferably 5-7:2-4:1, more preferably 5.5-6.5:2.5-3.5:1, and more preferably 6:3:1.

[0027] In the present invention, isobornyl acrylate (IBOA) has a moderate curing speed, high flexibility, light transmittance, low shrinkage, excellent impact resistance and heat resistance, and moderate hardness after curing. When cyclotrimethylolpropane formal acrylate (TMPTA-F) is used in combination with isobornyl acrylate, the shrinkage of the adhesive can be further reduced, the flexibility can be improved, and the adhesive has good wear resistance and crack resistance after curing. Ethoxylated acrylate (EOEA) has a low viscosity, which can effectively reduce the viscosity of the adhesive and improve the processing performance; it can also improve the leveling of the adhesive and reduce flow marks and uneven thickness during the coating process; the low shrinkage property of EOEA reduces the accumulation of internal stress during the curing process, and combined with the modified difunctional aliphatic polyurethane acrylate oligomer, it can effectively improve the crack resistance of the adhesive layer; EOEA also has photoinitiating ability, and can participate in polymerization in the free radical photocuring system to improve the physical properties of the adhesive layer.

[0028] In the present invention, the modified difunctional aliphatic urethane acrylate oligomer preferably comprises a polycaprolactone-modified difunctional aliphatic urethane acrylate oligomer, a polycarbonate-modified difunctional aliphatic urethane acrylate oligomer and a polyether-modified difunctional aliphatic urethane acrylate oligomer, and the mass ratio of the polycaprolactone-modified difunctional aliphatic urethane acrylate oligomer, the polycarbonate-modified difunctional aliphatic urethane acrylate oligomer and the polyether-modified difunctional aliphatic urethane acrylate oligomer is 5 to 7:2 to 4:1, and more preferably 5.5 to 6.5:

[0029] 2.5-3.5:1, more preferably 6:3:1.

[0030] In the present invention, the difunctional aliphatic polyurethane acrylate oligomer is a multifunctional oligomer synthesized from aliphatic diisocyanate, diol and a capping agent with acrylic functional group (such as hydroxypropyl acrylate). Among them, the polycaprolactone-modified difunctional aliphatic polyurethane acrylate oligomer has high flexibility, low shrinkage and excellent crack resistance, and is suitable for use in application environments with large temperature differences to improve the flexibility and low-temperature crack resistance of the adhesive; the polycarbonate-modified difunctional aliphatic polyurethane acrylate oligomer has high adhesion, low shrinkage and excellent yellowing resistance, and is suitable for scenes with high adhesion requirements; the polyether-modified difunctional aliphatic polyurethane acrylate oligomer has high transparency, low shrinkage and good fluidity, and is suitable for thin layer coating and high transparency application scenes. The combination of polycaprolactone modified difunctional aliphatic polyurethane acrylate oligomer, polycarbonate modified difunctional aliphatic polyurethane acrylate oligomer and polyether modified difunctional aliphatic polyurethane acrylate oligomer can improve the adhesion, flexibility and low-temperature crack resistance of the adhesive layer while maintaining high transmittance, meeting the Mini LED packaging requirements.

[0031] In the present invention, the photoinitiator preferably comprises phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and the mass ratio of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide to ethyl 2,4,6-trimethylbenzoylphenylphosphonate is preferably 80 to 90:15, more preferably 82 to 88:15, and more preferably 85:15.

[0032] In the present invention, the photosensitizer is preferably 2-chlorothioxanthone or thioxanthone.

[0033] In the present invention, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide has excellent deep curing ability, and can continue to release free radicals after the light stops, achieving dark curing and delayed curing, and has high light transmittance and yellowing resistance. The photosensitizer and the photoinitiator work synergistically to extend the time for free radical generation, achieve a deeper curing effect, and ensure that the unirradiated area can also be fully cured.

[0034] In the present invention, the thermal initiator is preferably tert-butyl peroxypivalate or diisopropylbenzene peroxide. The thermal initiator is stable at room temperature and does not react spontaneously, but can slowly release free radicals under mild heat conditions (such as 60-80° C.) to achieve curing of the adhesive in the unirradiated area.

[0035] In the present invention, the light scattering filler is preferably nano titanium dioxide or nano silicon dioxide. Adding a small amount of light scattering filler can enhance the light scattering effect, enhance the propagation of light in the adhesive, and help further solidification of the unirradiated area.

[0036] The present invention also provides a method for preparing the high-efficiency UV-curable adhesive composition, comprising the following steps:

[0037] A high-efficiency ultraviolet light-curing adhesive composition is obtained by mixing monofunctional acrylate monomers, modified bifunctional aliphatic polyurethane acrylate oligomers, photoinitiators, photosensitizers, thermal initiators and light-scattering fillers.

[0038] In the present invention, the mixing temperature is preferably 30-50°C, more preferably 35-45°C, and more preferably 40°C; the mixing time is preferably 20-30min, more preferably 22-28min, and more preferably 25min; stirring is preferably performed during the mixing process, and the stirring speed is preferably 300-600rpm, more preferably 400-500rpm, and more preferably 450rpm.

[0039] The present invention also provides application of the high-efficiency UV-curable adhesive composition in Mini LED packaging.

[0040] In the present invention, the application of the high-efficiency UV-curable adhesive composition in Mini LED packaging is preferably first cured by UV light irradiation, and the unirradiated area is further heated to 60-80° C. to activate the thermal initiator to achieve complete curing.

[0041] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0042] Example 1

[0043] The high-efficiency ultraviolet light-curing adhesive composition comprises the following components in parts by weight:

[0044]

[0045] The monofunctional acrylate monomers include isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate in a mass ratio of 6:3:1;

[0046] The modified bifunctional aliphatic urethane acrylate oligomer comprises polycaprolactone-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8402, polycarbonate-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8800 and polyether-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8701 in a mass ratio of 6:3:1;

[0047] The photoinitiator comprises phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate in a mass ratio of 85:15;

[0048] The photosensitizer is 2-chlorothioxanthone, the thermal initiator is tert-butyl peroxypivalate, and the light scattering filler is nano titanium dioxide.

[0049] The preparation method of the high-efficiency UV-curable adhesive composition is as follows: monofunctional acrylate monomers, modified bifunctional aliphatic polyurethane acrylate oligomers, photoinitiators, photosensitizers, thermal initiators and light scattering fillers are stirred and mixed at 40° C. and 500 rpm for 25 minutes to obtain the high-efficiency UV-curable adhesive composition.

[0050] Example 2

[0051] The high-efficiency ultraviolet light-curing adhesive composition comprises the following components in parts by weight:

[0052]

[0053]

[0054] The monofunctional acrylate monomers include isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate in a mass ratio of 5:4:1;

[0055] The modified bifunctional aliphatic urethane acrylate oligomer comprises polycaprolactone-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8402, polycarbonate-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8800 and polyether-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8701 in a mass ratio of 7:2:1;

[0056] The photoinitiator comprises phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate in a mass ratio of 80:15;

[0057] The photosensitizer is thioxanthone, the thermal initiator is dicumyl peroxide, and the light scattering filler is nano-silicon dioxide.

[0058] The preparation method of the high-efficiency UV-curable adhesive composition is the same as that of Example 1.

[0059] Example 3

[0060] The high-efficiency ultraviolet light-curing adhesive composition comprises the following components in parts by weight:

[0061]

[0062] The monofunctional acrylate monomers include isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate in a mass ratio of 7:2:1;

[0063] The modified bifunctional aliphatic urethane acrylate oligomer comprises polycaprolactone-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8402, polycarbonate-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8800 and polyether-modified bifunctional aliphatic urethane acrylate oligomer Ebecryl 8701 in a mass ratio of 5:4:1;

[0064] The photoinitiator comprises phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate in a mass ratio of 90:15;

[0065] The photosensitizer is 2-chlorothioxanthone, the thermal initiator is tert-butyl peroxypivalate, and the light scattering filler is nano titanium dioxide.

[0066] The preparation method of the high-efficiency UV-curable adhesive composition is the same as that of Example 1.

[0067] Comparative Example 1

[0068] The difference from Example 1 is that the monofunctional acrylate monomer is only isobornyl acrylate.

[0069] Comparative Example 2

[0070] The difference from Example 1 is that the monofunctional acrylate monomer comprises isobornyl acrylate and cyclotrimethylolpropane formal acrylate in a mass ratio of 7:3.

[0071] Comparative Example 3

[0072] The difference from Example 1 is that the monofunctional acrylate monomer is only cyclotrimethylolpropane formal acrylate.

[0073] Comparative Example 4

[0074] The difference from Example 1 is that the modified bifunctional aliphatic polyurethane acrylate oligomer is only the polycaprolactone-modified bifunctional aliphatic polyurethane acrylate oligomer Ebecryl 8402.

[0075] Comparative Example 5

[0076] The difference from Example 1 is that the modified difunctional aliphatic polyurethane acrylate oligomer is only polycarbonate-modified difunctional aliphatic polyurethane acrylate oligomer Ebecryl 8800.

[0077] Comparative Example 6

[0078] The difference from Example 1 is that the modified difunctional aliphatic polyurethane acrylate oligomer is only the polyether-modified difunctional aliphatic polyurethane acrylate oligomer Ebecryl 8701.

[0079] Comparative Example 7

[0080] The difference from Example 1 is that the photosensitizer, thermal initiator and light scattering filler are omitted.

[0081] The viscosity of the adhesive compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was tested at 25° C. in accordance with GB / T 2794-2022. The test results are shown in Table 1.

[0082] The curing performance test of the adhesive compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was carried out respectively. The curing conditions were as follows: the adhesive composition with a thickness of 1 mm was coated on the substrate and placed under a power of 100 mW / cm 2 , irradiated under ultraviolet light with a wavelength of 365nm for 15s, shielded the adhesive surface, and then heated at 60℃ for 30min for dark curing. The cured adhesive layer was tested for Shore hardness D, curing depth, and transmittance. Shore hardness D was tested in accordance with GB / T 531.1-2008, curing depth was tested in accordance with ISO 4049:2019, and transmittance was tested in accordance with GB / T 2410-2008. The test results are shown in Table 1.

[0083] The cured adhesive layer was subjected to an aging performance test at 80°C for 100 hours. After aging, the light transmittance of the adhesive layer was tested in accordance with GB / T 2410-2008. The test results are shown in Table 1.

[0084] The cured adhesive layer was subjected to a temperature stability test, with the conditions of placing it at a low temperature of -40°C for 2 hours, and then placing it at a high temperature of 80°C for 2 hours. This was one cycle, and it was repeated 500 times. After the cycle, the peel strength of the adhesive layer was tested according to ISO 4587:2003, and the crack rate was recorded. The test results are shown in Table 1.

[0085] Table 1 Adhesive composition performance test results

[0086]

[0087] The high-efficiency UV-curable adhesive composition of the present invention introduces ethoxylated acrylate, so that the adhesive composition has a lower viscosity, which is significantly lower than that of Comparative Examples 1 to 3, and meets the high-precision coating requirements in MiniLED packaging. The curing depth of the high-efficiency UV-curable adhesive composition of the present invention reaches 2.8 mm, which is significantly better than that of Comparative Examples 1 to 7, which is due to the low shrinkage of ethoxylated acrylate and the synergistic effect of light-scattering fillers. The light transmittance of the adhesive layer of the high-efficiency UV-curable adhesive composition of the present invention after curing reaches 93%, and it still maintains 91% after aging, which is significantly higher than that of Comparative Examples 1 to 7. This is mainly based on the synergistic effect between ethoxylated acrylate and three modified difunctional aliphatic polyurethane acrylate oligomers; on the contrary, the light transmittance of Comparative Examples 1 to 7 is less than 90%, and the light transmittance is reduced to 83 to 87% after aging. The high-efficiency UV-curable adhesive composition of the present invention has excellent temperature stability. After the cycle test from low temperature -40°C to high temperature 80°C, there is no crack on the surface, and the peel strength reaches 1.2N / mm, which is significantly higher than the comparative example.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-efficiency UV-curable adhesive composition, characterized in that: Contains the following components by mass:

2. The high-efficiency UV-curable adhesive composition according to claim 1, characterized in that: The monofunctional acrylate monomers include isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate, and the mass ratio of isobornyl acrylate, cyclotrimethylolpropane formal acrylate and ethoxylated acrylate is 5-7:2-4:

1.

3. The high-efficiency UV-curable adhesive composition according to claim 2, characterized in that: The modified difunctional aliphatic urethane acrylate oligomer comprises a polycaprolactone-modified difunctional aliphatic urethane acrylate oligomer, a polycarbonate-modified difunctional aliphatic urethane acrylate oligomer and a polyether-modified difunctional aliphatic urethane acrylate oligomer, and the mass ratio of the polycaprolactone-modified difunctional aliphatic urethane acrylate oligomer, the polycarbonate-modified difunctional aliphatic urethane acrylate oligomer and the polyether-modified difunctional aliphatic urethane acrylate oligomer is 5 to 7:2 to 4:

1.

4. The high-efficiency UV-curable adhesive composition according to claim 2 or 3, characterized in that: The photoinitiator comprises phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and the mass ratio of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide to ethyl 2,4,6-trimethylbenzoylphenylphosphonate is 80-90:

15.

5. The high-efficiency UV-curable adhesive composition according to claim 4, characterized in that: The photosensitizer is 2-chlorothioxanthone or thioxanthone.

6. The high-efficiency UV-curable adhesive composition according to claim 5, characterized in that: The thermal initiator is tert-butyl peroxypivalate or dicumyl peroxide.

7. The high-efficiency UV-curable adhesive composition according to claim 5 or 6, characterized in that: The light scattering filler is nano titanium dioxide or nano silicon dioxide.

8. The method for preparing the high-efficiency UV-curable adhesive composition according to any one of claims 1 to 7, characterized in that: The following steps are included: A high-efficiency ultraviolet light-curing adhesive composition is obtained by mixing monofunctional acrylate monomers, modified bifunctional aliphatic polyurethane acrylate oligomers, photoinitiators, photosensitizers, thermal initiators and light-scattering fillers.

9. The preparation method according to claim 8, characterized in that: The mixing temperature is 30-50° C., the mixing time is 20-30 min, and stirring is performed during the mixing process at a stirring speed of 300-600 rpm.

10. Application of the high-efficiency UV-curable adhesive composition according to any one of claims 1 to 7 in Mini LED packaging.

Citation Information

Patent Citations

  • Ultraviolet curing adhesive composition for Mini LED (light-emitting diode) packaging as well as preparation method and application of ultraviolet curing adhesive composition

    CN114181660A

Cited By

  • PDLC coating glue as well as preparation method and application thereof

    CN121914673A

  • PDLC coating glue, its preparation method and application

    CN121914673B